Drugs influencing orthodontic tooth movement: An overall review - Kamatchi Diravidamani; Sathesh Kumar Sivalingam; Vivek Agarwal (Wolters Kluwer Medknow Publications, 2012)
Orthodontic treatment is based on the premise that when force is delivered to a tooth and thereby transmitted to the adjacent investing tissues, certain mechanical, chemical, and cellular events take place within these tissues, which allow for structural alterations and contribute to the movement of that tooth. Molecules present in drugs and nutrients consumed regularly by patients can reach the mechanically stressed paradental tissues through the circulation and interact with local target cells. The combined effect of mechanical forces and one or more of these agents may be inhibitory, additive, or synergistic. Current orthodontic research aims to develop methods of increasing the tissue concentration of molecules promoting tooth movement, while simultaneously decreasing the concentration of unwanted elements which can produce harmful side effects. This article discusses in detail the various possible drugs that can bring about alterations in the desired orthodontic tooth movement.